2017
DOI: 10.1016/j.clinbiochem.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum anti-heat shock protein 27 antibody levels and obesity

Abstract: We have found that serum anti-HSP27 antibody titers are related to several cardiovascular risk factors, necessitating further studies on the value of this emerging marker for risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…Sahebkar et al showed an increase in anti-HSP27 antibody levels in patients with coronary heart disease (CHD) and MetS compared to individuals with CHD alone (Sahebkar et al 2011), which is in agreement with the study of Ghayour-Mobarhan et al (25). Kargari et al found that obese individuals showed significantly higher anti-HSP27 antibody levels than the non-obese group (26). However, they did not find any association between anti-HSP27 antibody titers and either diabetes or MetS.…”
Section: Discussionsupporting
confidence: 63%
“…Sahebkar et al showed an increase in anti-HSP27 antibody levels in patients with coronary heart disease (CHD) and MetS compared to individuals with CHD alone (Sahebkar et al 2011), which is in agreement with the study of Ghayour-Mobarhan et al (25). Kargari et al found that obese individuals showed significantly higher anti-HSP27 antibody levels than the non-obese group (26). However, they did not find any association between anti-HSP27 antibody titers and either diabetes or MetS.…”
Section: Discussionsupporting
confidence: 63%
“…HSPB1 (also known as HSP27) serves as an ATP-independent chaperone [ 30 ]. In mammals, it has been reported that obese subjects had higher anti-HSP27 antibody levels [ 31 ], and induction of HSP27 may blunt the adverse effect of fat overexposure on insulin function [ 32 ]. In diabetic hearts, the phosphorylation of HSP27 enhanced lipoprotein lipase activity and promoted hydrolysis of triglyceride-rich lipoproteins to fatty acids [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-two seronegative healthy individuals, as a part of the large MASHAD Cohort Study [15], were enrolled as subjects without CHB, at the aforementioned time. They were recruited based on age and gender matching and were proven negative for HBV, HCV, and HDV by serology examinations (Diapro HBsAg, HCV Ab, HDV Ab ELISA Kits, Italy).…”
Section: Study Populationmentioning
confidence: 99%
“…The lower limit of HBV DNA quanti cation for this assay was 100 copies/mL. Blood sample collection and laboratory analysis for subjects without CHB, have been conducted with the same protocols as a part of the MASHAD Cohort Study [15], carried out at Mashhad University of Medical Sciences, and the whole related data was transferred to our study.…”
Section: Sample Collection and Laboratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation